Effect of deficiency-adjusted macronutrients to cure brown bast syndrome in rubber trees (Hevea brasiliensis) - Ahmad, Nurul Atiqah; Sulaiman, Zulkefly; Abdul Samad, Mohd Yusoff; Rezaul Karim, Sarker Mohammad; Salisu, Monsuru Adekunle (Universiti Putra Malaysia Press, 2023)
The brown bast (BB) syndrome causes a 15-20% loss of annual rubber (Hevea brasiliensis) production in Malaysia, and no sustainable remedy has been developed yet. Initial investigation showed a macronutrients deficiency in the bark of affected plants compared to non-affected plants. Therefore, this study was undertaken to know the effect of spraying the deficient macronutrients in curing BB syndrome and increasing latex productivity. The treatments were selected by adjusting deficient nutrients, especially in N, K, and S, compared to healthy plants. The treatments consisted of 13 combinations of nutrient concentrations and a control (no application on healthy rubber trees). One liter of individual treatment per tree was applied on the trunk of BB-affected trees once a week for one month. Data on latex production was collected one week after the last application and continued for up to three months. The results showed that the treatment T9 (0.5% N, 0.8 mg/L K, and 0.2% S), in addition to other prescribed nutrients, made a 100% cure of BB syndrome after three weeks of application, and the nutrient contents of the bark of the affected plants appeared to be similar to the healthy plants. Applying these additional nutrients enhanced the latex production at the rate of 51.85 g/tapping/tree after two months of treatment application under the agro-ecosystem of FELCRA, Simpang Renggam, Johor, Malaysia. It is a new finding to 100% cure BB syndrome and to increase the latex productivity in sustaining the rubber industry in Malaysia.